1977
DOI: 10.1164/arrd.1977.116.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, Socioeconomic Status, and Chronic Respiratory Disease1,2

Abstract: Prevalence rates of chronic bronchitis and asthma and mean levels of ventilatory lung function were related to age, smoking habits, occupation, education, and income in 4,699 men and women living in Tecumseh, Michigan. The prevalence of chronic bronchitis was higher and mean levels of 1-sec forced expiratory volume were lower in cigarette smokers than in other men and women, and heavy smokers were affected more than light smokers. The prevalence of chronic bronchitis was higher and mean 1-sec forced expiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(46 citation statements)
references
References 2 publications
5
40
0
1
Order By: Relevance
“…However, earlier studies in which voluntary quitting smoking rate was low, showed that the level of FEV 1 in former smokers was generally the lowest [5,21,22]. Our analysis is consistent with these earlier studies.…”
Section: Discussionsupporting
confidence: 92%
“…However, earlier studies in which voluntary quitting smoking rate was low, showed that the level of FEV 1 in former smokers was generally the lowest [5,21,22]. Our analysis is consistent with these earlier studies.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of relation of asthma to exsmoking in relatives, although it was observed in the case/control component of the EGEA and although weaker in several general populations [4,22], supports the hypothesis that the pattern of smoking in families with asthmatics is complex. In the general population, it is well known that there is assortative marriage for smoking habits and that smoking habits in offspring are strongly influenced by parental smoking, but there is limited information on smoking habits in families with asthma.…”
Section: Discussionsupporting
confidence: 56%
“…It is recognized that maternal smoking is a risk factor for asthma in children [2] and that smoking increases the incidence of asthma in subjects exposed to some occupational agents [3]. However, there is conflicting evidence as to whether active smoking in general may be a risk factor for asthma, although there are more studies showing no association [4] than studies supporting that hypothesis [5]. The association between smoking and asthma is difficult to understand due to potential biases.…”
mentioning
confidence: 99%
“…However, with regard to an association of active smoking with asthma, the cross-sectional data are more equivocal. Cross-sectional studies, which are again subject to potential selection bias, have yielded both positive (14) and negative results (15)(16)(17). Longitudinal data, which are less subject to the potential of selection bias, are unequivocal in supporting a role of active smoking in asthma occurrence (18,19 1.6, 5.6) and current asthma (OR = 3.3; 95% CI: 1.7, 6.4).…”
Section: Natural History Of Asthmamentioning
confidence: 99%